2016
DOI: 10.1094/mpmi-05-16-0091-r
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic Burkholderia Species Show Diverse Arrangements of nif/fix and nod Genes and Lack Typical High-Affinity Cytochrome cbb3 Oxidase Genes

Abstract: Genome analysis of fourteen mimosoid and four papilionoid beta-rhizobia together with fourteen reference alpha-rhizobia for both nodulation (nod) and nitrogen-fixing (nif/fix) genes has shown phylogenetic congruence between 16S rRNA/MLSA (combined 16S rRNA gene sequencing and multilocus sequence analysis) and nif/fix genes, indicating a free-living diazotrophic ancestry of the beta-rhizobia. However, deeper genomic analysis revealed a complex symbiosis acquisition history in the beta-rhizobia that clearly sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 66 publications
7
47
0
Order By: Relevance
“…Nodulating strains of Cupriavidus contain nodA (Chen et al 2005) and other nod genes. The Cupriavidus nod genes are similar to each other and form a distinct clade suggesting that they most likely had a single origin from a neotropical (Mimosoid) Burkholderia ancestor (Andam et al 2007;Bontemps et al 2010;De Meyer et al 2016).…”
Section: Rhizobial and Nonrhizobial Bacteria That Fix Nitrogen And Nomentioning
confidence: 97%
See 2 more Smart Citations
“…Nodulating strains of Cupriavidus contain nodA (Chen et al 2005) and other nod genes. The Cupriavidus nod genes are similar to each other and form a distinct clade suggesting that they most likely had a single origin from a neotropical (Mimosoid) Burkholderia ancestor (Andam et al 2007;Bontemps et al 2010;De Meyer et al 2016).…”
Section: Rhizobial and Nonrhizobial Bacteria That Fix Nitrogen And Nomentioning
confidence: 97%
“…Agrobacterium. Cummings et al (2009) identified a nodulating strain isolated from nodules of Sesbania cannabina as Rhizobium radiobacter Chen et al (2001Chen et al ( , 2003Chen et al ( , 2005, De Meyer et al (2016) (Agrobacterium tumefaciens) IRBG74, and Youseif et al (2014) isolated agrobacterial strains carrying both nod and nif genes enabling them to elicit soybean nodulation upon reinoculation. Methylobacterium.…”
Section: Rhizobial and Nonrhizobial Bacteria That Fix Nitrogen And Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we determined that three Alpha-rhizobia genera, Bradyrhizobium, Rhizobium and Azorhizobium shared nodU and nodS (except for R. leguminosarum and R. etli), and in this context it is interesting that Sesbania spp. nodulate with Rhizobium and Azorhizobium [58], but so far are not reported to do so with Bradyrhizobium. However, Bradyrhizobium housed the widest range of host-specific genes, sharing them with most other Rhizobia discovered in our study, so it is possible that strains of Bradyrhizobium that can nodulate Sesbania spp.…”
Section: The Divergence In Symbiosis Genes Between Alpha and Betarhizmentioning
confidence: 93%
“…Although it is widely reported [58], some reports have indicated that horizontal gene transfer (HGT) has not been common even within Alpharhizobia, as revealed by the nodA and nodC phylogenies of some Ensifer and Rhizobium symbionts [8,31]. This lack of clarity as to the origin and evolution of symbiotic genes (nodulation and nitrogen fixation genes) in rhizobium sensu lato means that their origin/evolution in the Beta-rhizobia are still a subject of much debate.…”
mentioning
confidence: 99%